Attaining Doppler Precision of 10 cm s-1 with a Lock-in Amplified Spectrometer. (4th January 2016) - Jensen-Clem, Rebecca; Muirhead, Philip S.; Bottom, Michael; Wallace, J. Kent; Vasisht, Gautam; Asher Johnson, John
Abstract: We explore the radial velocity performance benefits of coupling starlight to a fast-scanning interferometer and a fast-readout spectrometer with zero readout noise. By rapidly scanning an interferometer, we can decouple wavelength calibration errors from precise radial velocity measurements, exploiting the advantages of lock-in amplification. In a Bayesian framework, we investigate the correlation between wavelength calibration errors and resulting radial velocity errors. We construct an end-to-end simulation of this approach to address the feasibility of achieving 10 cm s -1 radial velocity precision on a typical Sun-like star using existing, 5 m-class telescopes. We find that such a precision can be reached in a single night, opening up possibilities for ground-based detections of Earth-Sun analog systems.